Considerations on amino acid patterns in the natural felid diet: a review - Sun, Mengmeng; Cuyper, Annelies De; Dierenfeld, Ellen S.; Janssens, Geert P. J. (Frontiers in Veterinary Science, 2024)
Amino acids are essential for the growth, development, and reproduction of carnivores. This literature review summarizes the amino acid patterns of different raw diets including whole prey, body tissue and muscle for felids under human care. In general, natural prey (and its parts) meet the minimum essential amino acid requirements outlined by the National Research Council for adult cats. On a whole-prey diet, lysine and methionine far exceed requirements, while histidine approaches the minimum threshold. However, histidine concentration is higher in muscle meat. Body tissues, except for the skin, demonstrate no deficiency in essential amino acids. Notably, non-essential amino acids are found in raw meat diets in elevated concentrations, and their levels remain stable, akin to those of essential amino acids. Although felid requirements for non-essential amino acids are not specified, attention should be paid to their role in nutrition. While the amino acid patterns of diverse raw diets show no significant variation, the impact of prolonged single-source protein may require attention.